Conceptual models of andesitic volcanic aquifers developed through a muti-proxy approache - Baud, Benjamin (CCSD, 2024)
Volcanic areas represent only 7% of the emerged rocks. Still, they are widespread worldwide, including in Iceland, Russia, Indonesia, the Andes, the Cascades, etc.… In volcanic areas, the aquifers usually provide a good quality of water, abundant and constant over the years. However, a synthesised compilation of several HCMs in the world is highlights that there is no generic conceptual model for the andesitic environment. Such generic conceptual model is broadly use in basaltic environment. The work performed in this PhD show that several standard features can be synthesised into a Generic Hydrogeological Conceptual Model (GCHM). This GHCM relies mainly on the distribution of the lateral facies from the top of a volcano to its feet. The GHCM is then divided into Central, Proximal, Medial, and Distal zones, constituting a “continuum”. Each zone has a dominant type of rock. Consequently, the properties of the aquifers change from one zone to another. Moreover, the PhD is part of a broader project focused on studying the groundwaters of the Arjuno-Welirang volcanic complex in Java, Indonesia. Despite the significant use of groundwaters in the area, the volcanic complex must be thoroughly examined. Local partners have noted a decline in the discharge of some springs and the water levels in artesian borewells, coinciding with the growth of local industrial and touristic activities. The new insights allow us to divide the Arjuno Welirang Volcanic complex in several HCM based on the GHCM, following upstream-downstream axis. The sub-division of the mountain is the fruit of a multi-disciplinary research, including geological, geophysical, geomorphological, hydrological and hydrogeochemical data. This study supports the preponderance of the geological structures on the groundwater behaviour in a volcanic-complex. Indeed, specific river loss linked to geological specificities have been highlighted. And each volcanic edifice shows specific groundwater patterns.This research improved the general scientific knowledge on the ...